Past, Current and Future Trends in Tobacco Use - Guindon, G. Emmanuel; Boisclair, David (World Bank, Washington, DC, 2013)
This paper first estimates the number of tobacco users in 2000 and cigarette consumption from 1970 to 2000 by regions and levels of development and briefly discusses the advantages and disadvantages of estimating tobacco use on the basis of prevalence surveys or aggregate data. Secondly, prevalence (and its associated number of smokers) and cigarette consumption (total and per capita) are projected in the future using several scenarios of changes in tobacco use (prevalence and cigarette consumption), as well as different assumptions about population and income growth. The results show that even if all countries immediately implement a comprehensive set of tobacco control policies, the reduction in the number of tobacco users and the total consumption of cigarettes will be gradual. This should give comfort to farmers and others who fear the impact of tobacco control on their livelihoods. It is however, discouraging news for public health, since it implies that the number of tobacco attributable deaths will continue to rise for decades to come.